An ATF/CREB binding motif is required for aberrant constitutive expression of the MHC class II DR alpha promoter and activation by SV40 T-antigen. - Cox, P M (1992)
Constitutive expression of major histocompatibility complex class II (MHC II) antigens normally occurs in B-lymphocytes and antigen presenting cells of the monocyte/macrophage lineage. However, many malignant tumours and transformed cells express these proteins aberrantly. We demonstrate here that the MHC II DR alpha promoter is constitutively active both in the SV40 large T antigen transformed cell line, COS, and in CV1 cells from which they are derived. As an approach to understanding the molecular mechanisms underlying aberrant DR alpha expression we have examined the cis- and trans-acting requirements for DR alpha transcription in these cell types. Electrophoretic mobility shift assays showed that the region immediately 3' to the X-box was bound by a member of the ATF/CREB family of transcription factors. Using deletions and point mutations in the DR alpha promoter we demonstrate that, in contrast to B-cells, the octamer motif and conserved X- and Y-boxes make only a minor contribution to promoter function while single point mutations in the ATF/CREB motif reduced transcription up to 20-fold. In addition, we show that the DR alpha promoter is activated by SV40 large T-antigen and that activation requires an intact ATF/CREB motif. Similar data were obtained using B16 melanoma cells. These results suggest that the ATF/CREB motif may be a target for transcription deregulation in several transformed cell types.